Morte e vida João Pessoa: imaginário social e cotidiano nos discursos jornalísticos - Nascimento, Flávia Lopes Sales do (2019)
The social imaginary concept could be understood as a group of sings and symbols produced in a cultural and social area. The cultural references and symbolical on groups are what gives an identify to a society. For Gilbert Durand, the Imaginary resembles to a ‘semantic bowl’, as a metaphor that uses the water fluidity to represent the potentiality of imaginary to spread out concepts and knowledge. Everything that interacts, cooperates and influences the production of knowledge of the social beings can be an interference to the symbolic social imaginary. So then, the anthropological imaginary grammar its used for understandings, from Durand, as theory and methodology for comprehension how the social imaginary of João Pessoa city have been represented in the two most known local presses: Jornal A União and Jornal Correio da Paraiba. This question above, had as main objective to identify the images of life and death on João Pessoa’s at Newspapers press, and cataloging them onto two ways, night and day regimes from the images of the anthropological imaginary path. The images of life are among on groups as discursive images (texts) and iconic (images and pictures etc.) that shows movement of the city, which can be seen both as negatively and positively. But the images of death (discursive or iconic) are understanding as images related to death as well known, or the symbolical death of João Pessoa, representing a chaos, causing a symbolical disenchantment of the city. With the quantitative method of the analysis of the content 254 newspapers texts that spoken about João Pessoa were collected, to verify these images in which regime it’s been connected. At general have been found more life images (59,1%) than death images (24,8%) on the News. Besides that, mostly of the texts showed day regime characteristics (61,8%) and night regime (29,1%) what brings a larger panorama of how João Pessoa it’s been show on these press medias: despite being a city of light and life, this urban center is axiomatic, contradictory and paradoxical, because in the course of the research we found that there is life in the middle of chaos and also there is death that gives a feeling of calm. So , the concepts of life and death are subjective and isn’t Always that they could be understood a maniqueism form, how it normally happens, it’s this way found on this research about João Pessoa social imaginary’s itself.